Pedagogical-Psychological Significance of Organizing Education in Pre-School Educational Institutions - Tosheva, N. T.; Rakhmatova, G. M. (European Journal of Life Safety and Stability (2660-9630), 2022)
In this article, the pedagogical -psychological significance of the organization of education in preschool educational institutions, on the basis of the educational process, taking into account age and individual characteristics - raising a mature generation, forming the free thinking of the child and preparing him for social life, and increasing their activity in the educational process, were purposefully analyzed.